1998
DOI: 10.1161/01.cir.97.21.2146
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Relative Dispersion but Blunted Stimulation of Mean Flow, Absolute Dispersion, and Blood Volume by Insulin in Skeletal Muscle of Patients With Essential Hypertension

Abstract: True flow heterogeneity, as judged from the coefficients of variation (relative dispersion), was comparable between the groups basally and during hyperinsulinemia. We conclude that mean flow, its absolute dispersion, and blood volume exhibit insulin resistance in patients with essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 68 publications
2
18
1
Order By: Relevance
“…Using a very different approach-PET scanning after inhalation of labeled CO-Raitakari et al (47) measured leg muscle blood volume before and during systemic insulin infusion (5 mU ⅐ kg Ϫ1 ⅐ min Ϫ1 ) in healthy volunteers and later in type 1 diabetic patients (12) and hypertensive subjects (48). The supraphysiologic insulin levels resulted in large increases in total leg blood flow and small (ϳ10%) but significant increases in blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…Using a very different approach-PET scanning after inhalation of labeled CO-Raitakari et al (47) measured leg muscle blood volume before and during systemic insulin infusion (5 mU ⅐ kg Ϫ1 ⅐ min Ϫ1 ) in healthy volunteers and later in type 1 diabetic patients (12) and hypertensive subjects (48). The supraphysiologic insulin levels resulted in large increases in total leg blood flow and small (ϳ10%) but significant increases in blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…We have found only short-term studies, relative to rapid weight loss, reported in the literature. It has been reported that water content, a potential reflection of nutritive blood flow (112,142), was increased after a 15.6-kg weight loss over a 9-wk period, suggesting that improved insulin sensitivity may contribute to improve ATBF (110). Recently, rapid weight loss in healthy obese subjects on very low caloric intake diets induced no modification of ATBF when expressed per gram of mass (181).…”
Section: ·Minmentioning
confidence: 99%
“…This notion is supported by the significant relationship between changes in IMV and ⌬GDR. The idea that coupling exists between insulin's vascular and metabolic actions is also underscored by the observation that IMV is impaired under conditions of IR as diverse as hypertension (32,33), polycystic ovary syndrome (34), obesity (18), or type 2 diabetes (5). Our findings contrast with those of Vollenweider et al (13) who measured the effect of FFA elevation on IMV in the calf.…”
Section: Fig 2 Effect Of Short-term (A) and Long-term Elevation (B)mentioning
confidence: 99%